The real effects of bank capital requirements - Henri Fraisse; Mathias Lé; David Thesmar (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We measure the impact of bank capital requirements on corporate borrowing and investment using loanE level data. The Basel II regulatory framework makes capital requirements vary across both banks and across firms, which allows us to control for firmE level credit demand shocks and bankE level credit supply shocks. We find that a 1 percentage point increase in capital requirements reduces lending by 10%. Firms can attenuate this reduction by substituting borrowing across banks, but only partially. The resulting reduction in borrowing capacity impacts investment, but not working capital: Fixed assets are reduced by 2.6%, but lending to customers is unaffected.
Keywords: E51; G21; G28; 330; Bank capital ratios; Bank regulation; Credit supply